Epidemiological characteristics of chronic obstructive pulmonary disease in the Middle Volga Region - Sergey Anatol'evich Babanov; S A Babanov (Терапевтический архив, 2011)
Aim. To study epidemiology and risk of chronic obstructive pulmonary disease (COPD) in environmental and climatic conditions of a large industrial center of the Middle Volga Region (the city of Samara). Material and methods. The questionnaire survey was made in 2063 participants (903 males and 1160 females, the response rate 73.68%) divided into four age groups: 30-39, 40-49, 50-59, 60 years and older. The epidemiological study employed the standard questionnaire based of European coal and Steel Association questionnaire (1993). All the patients with identified respiratory problems were examined clinically and functionally to verify COPD diagnosis. Results. High COPD rate was detected in Samara - 14.49% of 2063 males and females examined (18.72% in males and 11.21% in females, p < 0.001). Leading COPD risk factors include old age, male gender, tobacco smoking, prior respiratory infections, chronic diseases of the upper respiratory tract, polluted environment, unmarried status, low education, alcoholism. Conclusion. Prevalence of COPD in population of Samara is close to that in other large industrial centers of Russia but lower than in larger cities of Europe and in populations of industrial workers. It depends on the age and has special characteristics in males and females.